MENINGKATKAN KETERAMPILAN SENAM MERODA MELALUI PERMAINAN TALI PADA SISWA KELAS VIIIA MTS MA’ARIF NU KEMIRI PURWOREJO - Kun Wuryantoro dan Nur Rohmah Muktiani (Jurnal Pendidikan Jasmani Indonesia, 2013)
This study aims to determine the enhancement of learning through rope games to improve their wheeling skills gradeVIIIA MTs Maarif NU Pecan Purworedjo in physical education subjects. This research is a class act. Subjects in thisstudy were all students in the class VIIIA MTs Maarif NU Pecan Purworedjo, which amounts to 32 students and is 2cycles and each cycle held 2 meetings. Data analysis techniques are used descriptive analysis. The instrument inthis study using observation sheets, questionnaires, interview guides were filled by students, teachers, and friendsobserver. The study concluded that learning through rope games can further enhance students’ skills in the wheelingfloor gymnastics practice. This is evidenced by the value of the practice has increased significantly. Indicator ofachievement is the KKM (minimum completeness criteria) is 75. Based on the test data value measures students’skills before getting a value less than 75 is 20 students or 62.5 % and the value of more than 75, there were 12students, or 37.5 %. After receiving the first action (cycle 1) students who scored less than 75 live 7 students or21.87 % so in this cycle there is an increase of 40.63 %, meaning students who achieve full KKM to 25 studentsor 78.13 %. In the second cycle students who scored less than 75 is not there or achieves an increase of 100 %.Keywords: Skills, Gymnastics, Wheeling, Rope Games.